The contribution of islamic education learning to the development of entrepreneurial soft skills in students in the society 5.0 era - Syaiful Hadi; Raharjo (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Islamic Religious Education (IRE) is an educational approach that emphasizes both cognitive understanding and mastery of spiritual values. In addition to this, IRE plays a crucial role in developing students' soft skills and nurturing their entrepreneurial spirit. In the context of Society 5.0, which is defined by technological advancements and human-centered innovation, students must be equipped with key competencies such as communication, creativity, collaboration, and decision-making, all grounded in religious values. Integrating IRE into the learning process allows students to cultivate empathy, responsibility, discipline, and a strong work ethic, which are essential for entrepreneurial success. This article aims to explore how adaptive and innovative IRE approaches can foster spiritual awareness and strengthen the entrepreneurial mindset of students in the face of global challenges. A qualitative descriptive approach was used, based on a literature study. The results show that the integration of Islamic values in IRE not only enhances students' spiritual development but also plays a significant role in their entrepreneurial growth. These findings emphasize that IRE provides a strategic framework for developing a more relevant educational ecosystem that can effectively address the evolving demands of the Society 5.0 era. By aligning Islamic values with entrepreneurial education, IRE contributes to creating well-rounded, socially responsible students prepared for success in the modern, technology-driven world.